Teachers’ And Student Teachers’ Perspectives On Reflective Practices In Teaching And Learning In Public Basic Schools In The Gomoa East District Of The Central Region Of Ghana - Osei, Ernest; Danso Mensah, Dominic Kwaku; Bampo, Judith (Advances in Social Sciences Research Journal, 2020)
The purpose of the study was to explore teachers’ and student teachers’ perspective on reflective practices in teaching and learning in public basic schools in the Gomoa East District of the Central Region of Ghana. The study adopted sequential explanatory design. The study employed the theory of John Dewey (1932) as its theoretical framework. The study employed sequential explanatory design. The population was made up of teachers and student teachers in the Gomoa East District. The study used purposive and simple random sampling procedures to select student teachers and teachers respectively. Structured questionnaires and interview guides were used to gather data from one hundred and twenty nine (129) participants. Descriptive statistics such as simple frequency counts and percentages were used to analyse the quantitative data while content analysis was used to analyse the qualitative data. Finding from the study revealed that teachers understand the concept of reflective practices and its applications. Reflective practices enable teachers to reflect on their teaching experience. Reflective practices enable teachers to think about their knowledge in their subject area. Reflective practices help to improve teaching. Reflective practices provide direction on what could be done in future for professional growth and development. Reflective practices enable student teachers to engage in problem solving that helps to strengthen teaching ability. Findings from the study also indicate that there was inadequate in-service training for teacher and student teachers in the area of reflective practices. Strategies suggested to enhance reflective practice in teaching and learning were cordial relationship between teachers and student teachers, teachers and student teachers should encourage remedial teaching, effective collaboration in instructional activities between teachers and student teachers, teachers should provide adequate time for student teachers and supervise their performance, adequate in- service training for teacher and student teachers in the area of reflective practices and Regular support from headteachers, experience teachers and other educational stakeholders though mentorship and other teacher professional development programs.The study recommended that the Gomoa East District Education Directorate should organize intensive training in the area of reflective practices in teaching and learning for teachers and student teachers to enable them to gain adequate professional competencies to improve their teaching. Head teachers, experienced teachers and other educational stakeholders should readily offer support to ensure successful reflective practices in teaching and learning in schools. Finally, Ghanaian University Colleges of Education should offer teacher education programs or courses that teach pre-service teachers how to develop higher order thinking skills and how to critically reflect.